THE INFLUENCE OF SERVICESCAPE ON CUSTOMER SATISFACTION Study on Monopoly café and resto Jl. Merbabu No. 21, Malang - Dewi, Rizmia; Rohman, Fatchur (Jurnal Ilmiah Mahasiswa FEB, 2016)
This  research aims  to examine  the  influence  of  servicescape  on  customer satisfaction, a study on Monopoly café and resto Jl. Merbabu No 21, Malang. The type of this research is explanatory research, in accordance with purpose to describe the casual relationship among variables though hypothesis testing.  In this research used 120 samples, the sample and population were the customer of Monopoly café and resto. In this research, the data collection method is conducted through questionnaire distribution. The sampling  technique used  purposive sampling. Testing method in this research used Validity Test, Reability test and Classical Assumption Test. Analysis method in this research are multiple regression analysis and hypothesis testing used T test, F test, and dominant test with program SPSS for windows 16.0.  The result of this research showed that by partially analysis used T test can be concluded that Ambient Conditons, Space and Funtionally, Signs, Symbols, and Artifacts has significant effect on Customer Satisfaction. Further, the simultaneous analysis used F test can be concluded that variables Ambient Conditons, Space and Funtionally, Signs, Symbols, and Artifacts  together have significant effect on Customer Satisfaction. The dominant test showed that Space and Functionally is the dominant effect on Customer Satisfaction. The new fact in this research showed that respondent agreed  enough of Ambient Conditions, Space and Functionally, Signs, Symbols and Artifact on Monopoly cafe and resto  is good enough and  influence customer to be satisfied to Monopoly cafe and resto Key Words:  Servicescape, Ambient Conditions, Space and Functionally, Signs, Symbols, Artifacts, Customer Satisfaction